2021
DOI: 10.22207/jpam.15.4.45
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Potential and Chemical Profiling of Leaves Essential Oil of Mentha Species Growing under North-West Himalaya Conditions

Abstract: Mentha essential oil is one of the most utilized essential oil in the food and pharmaceutical industries. The present study reports the chemical composition and antibacterial properties of leaf essential oils of Mentha species. Further, the effect of the harvesting period on essential oil yield was also investigated. Firstly, the cultivated Mentha piperita and wild Mentha longifolia, revealed significant differences in their chemical profile. M. longifolia essential oil was characterized with endo-borneol (1.1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 43 publications
(50 reference statements)
0
4
0
Order By: Relevance
“…The study reported a sufficient amount of oil composition, varying from 0.63% germacrene-D to 51% menthol. This indicates that Mentha species contain menthol in maximum quantity [ 46 ]. Therefore, the plant has the potential to be used as a medicinal ingredient in the food industry to reduce the risk of cardiovascular diseases.…”
Section: Essential Oil and The Chemical Composition Of The Studied Sp...mentioning
confidence: 99%
See 1 more Smart Citation
“…The study reported a sufficient amount of oil composition, varying from 0.63% germacrene-D to 51% menthol. This indicates that Mentha species contain menthol in maximum quantity [ 46 ]. Therefore, the plant has the potential to be used as a medicinal ingredient in the food industry to reduce the risk of cardiovascular diseases.…”
Section: Essential Oil and The Chemical Composition Of The Studied Sp...mentioning
confidence: 99%
“…The same study reported 12 essential oil compounds in M. longifolia with different concentrations of oil compounds from April to July. Another study reported pulegone (86.64%) as a major constituent from M. pulegium , possessing antioxidant, quorum sensing, antiinflammatory and antimicrobial activities, indicating that the plant has the potential to reduce the risk of cardiovascular diseases [ 46 ]. The chemical composition of Peppermint oil was reported to include oxygen-containing substances, such as menthone (20%), menthol (45–50%), and sesquiterpenes about 3% [ 47 ].…”
Section: Essential Oil and The Chemical Composition Of The Studied Sp...mentioning
confidence: 99%
“…Mint essential oil (EO) has been reported to have a strong antimicrobial activity against several pathogenic microorganisms [10,11]. Many researchers have studied the biological activity of different EOs from Mentha against different pathogenic fungi, especially Fusarium species [11][12][13][14][15]. In particular, the two studied Mentha EOs have illustrated a strong antifungal activity against potato pathogens in addition to different soil-borne diseases in tomatoes [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…3 EO from medicinal plants exhibited bactericidal, virucidal, and fungicidal activities and has several constituents responsible for the growth inhibition of many pathogenic microorganisms like bacteria, viruses, fungi, and protozoa. 4 EO's use is a promising approach to combat the growth of many foodborne pathogens and multiple drug-resistant microorganisms. There are wide applications of EO in food safety and preservation to increase its shelf-life 5 and limit the use of synthetic additives.…”
Section: Introductionmentioning
confidence: 99%